CO2 capture by biphasic absorbent–absorption performance and VLE characteristics. (15th March 2018) - Zhuang, Quan; Clements, Bruce
Abstract: Amine dissolved in alcohol is one of the possible biphasic absorbents for CO2 capture. Monoethanolamine (MEA) and methylaminoethanol (MAE) in isooctanol and 1-heptanol, respectively, were tested as absorbents by using a self-made batch mode chemisorption apparatus. CO2 absorption vapour-liquid equilibrium (VLE) curves were obtained. Phase separation of the absorbent MEA in alcohols occurred readily upon CO2 absorption at the absorption temperature. The CO2 bubbling absorption tests indicated that MAE in the alcohols did not experience phase separation in the whole possible operating temperature range from ambient to 90 °C. The principle for identifying potential CO2 phase separation absorbents is by a good match of the relative strength of the polarity of the amines with the solvent (alcohol in this study), and its change upon CO2 absorption and/or on further temperature increase of the CO2 loaded absorbent. The VLE curves are one of the most important properties of a CO2 /absorbent system, based on which, some of the engineering design and operation conditions of a CO2 absorption process can be determined. Highlights: The CO2 absorption isotherms at 40 °C by non-aqueous MEA were obtained. The non-aqueous MEA experienced phase separation upon CO2 absorption at 40 °C. The non-aqueous MAE did not show phase separation at any possible temperature. The non-aqueous MEA could be further developed as phase separation absorbents.